Reading in Arabic Orthography: The influence of Short Vowels on Reading Accuracy and Comprehension of Poor and Normal Arabic Readers (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
Research conducted on strategies aimed at improving reading skills and comprehension among Arabic readers (Abu Rabia, 1997, 1998) reported on the contribution, of the addition of short vowels to Arabic texts, to both the acquisition of proper reading skills during early childhood, and to better reading comprehension among all ages. The findings were considered controversial. Such a determination can have important implications for both local and national educational policies seeking the improvement of reading skills and comprehension among Arabic readers of all ages. In this study, 60 native Arabic speakers, 12 years old were sampled from school in northern Israel. They were divided into two equal groups of 30 normal and 30 poor readers, based on their average grade point average in the Arabic Language subject. The results indicated that the vocalization of Arabic texts significantly improved both reading accuracy and comprehension among all participants, whether normal or weaker readers. Further, despite the very noticeable difference between reading abilities among the two groups (regular and weak readers) at the outset, on the average we found that the addition of short vowels helped both groups acquire basic reading skills. The findings indicated that the use of vocalized texts helps readers achieve higher reading comprehension levels among all types of readers.